Digital transformation with cloud computing - Ng, Zhi Wei (2019)
Due to the advancement in Artificial intelligence (AI) and Machine Learning (ML), our ability to make brain-like machines has also advanced. The ideology behind AI being simply a robot programmed to do mundane tasks for us is no more. Over the last decade, the immense popularity of video hosting websites like YouTube, Dailymotion, Vimeo and social networks like Facebook, Twitter, Instagram, have galvanized extensive amount of video contents over the Internet. Therefore, this report will provide an understanding on how we could organize the growing number of videos on the web and extract important data that is interesting and useful to the user by using AI and ML. Cloud computing, latest technology methodologies and framework will also be discussed and used in order to make the project more scalable and productive in the real world today.